ROLE OF NGO IN FILLING THE GAP OF GOVERNMENT (A Case Study of Indus Resource Centre khairpur, Sindh Pakistan) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Role of non- government organization in filling the gap of government was studied through a study conducted on Indus Resource Centre. Government gap is created when some areas are being deprived of Government efforts. The objectives of research were firstly; to analyze the role of IRC in filling the gap of Government and to find out at what extend IRC is effective in fulfilling the needs of rural people. Data was taken from the majority of beneficiaries of the IRC and it was analyzed through the exploratory factor analysis technique with the help of SPSS 16.The overall analysis of study reveals that IRC plays very important role in filling the gap and it is very effective in fulfilling the needs of rural people by providing education facilities, human right awareness, sustainable livelihood, health and disaster management.